2018
DOI: 10.1177/0194599818764651
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Neutrophil‐to‐Lymphocyte Ratio in Patients with Human Papillomavirus–Positive Oropharyngeal Cancer

Abstract: Objective To investigate the prognostic impact of the neutrophil-to-lymphocyte ratio (NLR) for human papillomavirus-positive oropharyngeal cancer (HPV+ OPC). Study Design Retrospective institutional database analysis. Setting Tertiary referral medical center. Material and Methods In total, 104 patients with HPV+ OPC were enrolled. From the blood laboratory data checked within 4 weeks before initiation of primary treatment, NLR was calculated. The association between clinicopathological characteristics and NLR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 38 publications
2
27
2
Order By: Relevance
“…This cut-off has also been employed in prospective studies, confirming a prognostic role for this biomarker in head and neck malignancies (Kim et al, 2017;Moon et al, 2016;Zeng et al, 2016). However, those studies considered patients with different primary sites of head and neck districts, and only few reports have been published on OPC only (Huang et al, 2015;Jensen et al, 2017;So et al, 2018). In our study, NLR was associated only with worse OS independently of all known prognostic factors, confirming the literature findings mentioned above.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This cut-off has also been employed in prospective studies, confirming a prognostic role for this biomarker in head and neck malignancies (Kim et al, 2017;Moon et al, 2016;Zeng et al, 2016). However, those studies considered patients with different primary sites of head and neck districts, and only few reports have been published on OPC only (Huang et al, 2015;Jensen et al, 2017;So et al, 2018). In our study, NLR was associated only with worse OS independently of all known prognostic factors, confirming the literature findings mentioned above.…”
Section: Discussionsupporting
confidence: 89%
“…In one from So et al, a NLR > 2.42 predicted worse disease-free survival (So et al, 2018). In another one from Gorphe et al, in patients with p16-positive OPC, a NLR > 5 was correlated with worse OS and resulted to be an independent prognostic factor together with Hb level (Gorphe et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“… 7 , 9 15 The majority of studies have included a heterogeneous group of patients with tumours from differing head and neck subsites. 7 , 11 , 13 16 More recently, in a smaller study than ours, So et al 12 reported on a cohort of 104 patients with HPV-associated oropharyngeal cancer and showed that patients with high NLR had worse 5-year disease-free survival. In patients with HPV-negative disease, Lin et al 17 reported that an elevated NLR at 3 months after completion of radiotherapy was associated with worse survival.…”
Section: Discussionmentioning
confidence: 66%
“…The absence of these biomarkers is a limitation as it has been well documented that HPV or p16 positive oropharyngeal cancers typically have a better prognosis, a unique molecular signature, and a potentially distinct influence on the immune system given its virally mediated process. However, it should be noted that previous studies have examined the role of elevated NLR in HPV+ oropharyngeal squamous cell carcinoma and found an association between poor overall and cancer‐specific survival outcomes and increased NLR 5,36 . In this study, we controlled for upper airway inflammation using smoking and alcohol use as surrogate markers, however we were not able to account for other contributors to inflammation such as oral hygiene given the limited availability of that data.…”
Section: Discussionmentioning
confidence: 99%